Venetoclax-based combinations in AML and high-risk MDS prior to and following allogeneic hematopoietic cell transplant. Issue 14 (6th December 2021) - Bewersdorf, Jan Philipp; Derkach, Andriy; Gowda, Lohith; Menghrajani, Kamal; DeWolf, Susan; Ruiz, Josel D.; Ponce, Doris M.; Shaffer, Brian C.; Tamari, Roni; Young, James W.; Jakubowski, Ann A.; Gyurkocza, Boglarka; et al.
Abstract: The role of allogeneic hematopoietic cell transplant (allo-HCT) as consolidation after initial venetoclax therapy and the efficacy of venetoclax salvage therapy for relapse after allo-HCT in patients with acute myeloid leukemia (AML) are unclear. We conducted a retrospective study of patients with AML or myelodysplastic syndrome (MDS) who received venetoclax either before or after allo-HCT at Memorial Sloan Kettering Cancer Center and Yale University from 11 August 2016 to 16 November 2020. Among 39 heavily pretreated patients who received venetoclax before allo-HCT, median OS from allo-HCT was not reached after a median follow up of 12.5 months resulting in a 12-month OS estimate of 79.0%. In 37 patients who had received venetoclax-based combinations as salvage therapy after allo-HCT, the overall response rate was 32% with a median OS of 4.7 months (12-month OS estimate: 43.4%). Four patients underwent a second allo-HCT following venetoclax-based salvage therapy suggesting it as a potential salvage treatment option.